The Tilted Disc Syndrome. Issue 1 (1st February 2005) - Williams, Anna; Williams, Adrian; Austen, David
Abstract : Ten years ago, when I was a medical student, my father developed a neurological problem. He went for his regular eye test, but also had his visual fields checked on the new Humphrey Field Analyser recently bought by the optometrists. Trouble followed. The test was repeated in greater detail, and he appeared to have a bitemporal superior quadrantanopia (Fig. 1a). He was referred to his general practitioner who referred him on to the local neurology department for further investigation. More trouble followed as my parents telephoned me (the only faintly medical person in the family) to ask for the potential causes, tests, treatments, operations and outlook. My father was completely well, and had noticed no visual problem. My differential diagnosis then only consisted of one possibility – a pituitary tumour pressing on the optic chiasm. It had taken most of my second year at medical school to come to grips with